Treatment of anterior open bite caused by atypical swallowing habit - Mendoza Larrea, Valeria (2021)
The treatment of anterior open bite represents a challenge for orthodontist due the difficulty and instability of correction. This article presents the case of a 16-year-old male patient who attended the Dental Center of the San Martín de Porres University School of Dentistry - Specialty of Orthodontics, who presented class 1 malocclusion with anterior open bite . The patient received corrective treatment for the atypical swallowing habit, for which a palatal grid was used. Extractions of the upper and lower first premolars were also performed. At the end of the treatment, facial and dental changes were observed. The closure of the open bite was achieved, adequate alignment of the teeth, excessive protrusion of the upper and lower incisors and a correct occlusion were reduced. In the facial aspect, a notable improvement in the facial profile was observed, as well as a decrease in labial incopetence and the retraction of the upper and lower lip.